A influência da auto-eficácia na adesão aos comportamentos de saúde - Cardoso, Chrystiane Mendonça (2006)
This paper aimed to verify the prediction of self-efficacy in the adherence to health behaviors like: balanced diet, physical activities practice, stop smoking and reducing alcohol consumption. The participants were people with arterial hypertension and mellitus diabetes type 2, with age between 40 and 60 years old, patients from PSFs units. The data were analyside by descriptives statistics, correlations, standart linear regressions and logistics regressions. The results indicated that sticking to for all health behaviors are directly influenced by self-efficacy related to each health behavior. The data didn t show significant correlation between participation in health education meetings; self-efficacy and adherence to for all this health behaviors.